POTENTIAL ETHANOL OF Carica papaya L. EXTRACT AS IMMUNOMODULATORY THROUGH HISTOLOGY OBSERVATION AT MICE BALB/C SPLEEN - Tasminatun, Sri; Pravitasari, Ria; Makiyah, SN. Nurul (Fakultas Kedokteran Universitas Lambung Mangkurat, 2017)
Abstract: The diameter of the alba pulp of the spleen will be enlarged, when the body responds to allergens by increasing the activity of the immune system. Papaya fruits (Carica papaya L.) containing flavonoid that can be as an immunomodulator. This study aims to determine the effect of C. papaya extract to the diameter size alba pulp of the spleen of Ovalbumin (OVA) induced Balb/C mice. The research design was experimental in vivo animal test with post-test only control group design. Thirty male Balb/C mice, ±20grams weight, 8 weeks old, divided into six groups consists of a normal control, negative control, Methylprednisolone, and C. papaya extract treatment group (175mg/kg, 350mg/kg and 700mg/kg dose per day). The extract and Methylprednisolone are given for 28 days, while OVA is given on 15thand 22ndday (intraperitoneal,) and 23rd until 28thday (peroral). On the 29thday the mice are sacrificed and the duodenum was made into histological preparation with HE staining. The immunomodulator effect is assessed by the average of the diameter size alba pulp of the spleen under a light microscope. The data were analyzed using SPSS15 with one way ANOVA continued with Tukey test. The average of the diameter size alba pulp of the spleen for control group is 10,165 ± 0,195; negative control group is 30,357 ± 0,826; methylprednisolone group is 10,220 ± 0,346; 175mg/kgbb dose extract is 14,956 ± 1,057; 350mg/kgbb dose extract is 14,030 ± 0,667; and 700mg/kgbb dose extract is 12,504 ± 0,729. The conclusion of this study is Carica papaya L. extract treatment group (175mg/kg, 350mg/kg and 700mg/kg dose per day) has an effect to the average of the diameter size alba pulp of the spleen in OVA-induced Balb/C mice significantly. 700mg/kg dose per day has the same effect with the methylprednisolone group. Keywords: immunomodulator, Carica papaya L., alba pulp of the spleen, ovalbumin